When low beats high: Riding the sales seasonality premium - Grullon, Gustavo; Kaba, Yamil; Núñez-Torres, Alexander (Journal of Financial Economics, 2020)
This paper examines whether predictable seasonal patterns in firm fundamentals generate time variation in stock returns. Our findings indicate that stock returns are counterseasonal. Specifically, a long-short strategy of buying low-sales season stocks and shorting high-sales season stocks produces an annual alpha of 8.4% (14.5% over the last decade). This seasonal effect has a relatively high Sharpe ratio and occurs independently of previously documented seasonal anomalies. We analyze several possible hypotheses for this phenomenon.